GA-ANFIS PID compensated model reference adaptive control for BLDC motor - Murali Dasari; A Sreenivasula Reddy; M Vijaya kumar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
Adaptive control is one of the widely used control strategies to design advanced control systems for better performance and accuracy. Model reference adaptive control (MRAC) is a direct adaptive strategy with some adjustable controller parameters and an adjusting mechanism to adjust them. In this work Model Reference Adaptive Control for BLDC motors has been designed with a PID controller tuned by GA-ANFIS. GA-Trained ANFIS framework for tuning the PID controller has been proposed. This is used along with the MRAC to deliver enhanced performance in the control of BLDC motor. The performance of the proposed approach is validated for motor control under conditions of change in speed, change in load, change in inertia and change in phase resistance.. The performance is validated against convention PID and self tuning PID controllers. The result demonstrates a superior performance of the proposed approach